Analysis of Nominal and Verbal Metaphors in Robert Frost’s Selected Poems; A Corpus-Based Study - Zarhat Ali; Iqra Bibi; Farzia, (Dialogue Social Science Review (DSSR), 2024)
The intent of this investigation was scrutiny of the Nominal and Verbal metaphors used in Robert Frost’s selected poems. It emphasized on the identification and evaluation of the nominal and verbal metaphors in Robert Frost’s selected poems. First of all, the researcher identified the nominal and verbal metaphors through close reading, and the AntConc tool (Anthony,2023) was employed to gather information. Following the process of identifying both nominal and verbal metaphors, then the researcher proceeded to analyse them. The researcher found out what and how the metaphors conveyed their expressive meanings. The current study was based on the qualitative method, and Conceptual Metaphors’ theory was followed to analyse the nominal and verbal metaphors in Robert Frost’s selected poems. Nominal metaphors include, for instance, the term “road,” which denoted a choice or path. Examples of verbal metaphors was "two roads diverged," where "diverged" alluded to the paths splitting apart and the various choices that must be made throughout life.